Richard Scarry's please and thank you book. - Scarry, Richard (New York, Random House, 1973)
A series of stories featuring Huckle, Lowly, Pig Will, Pig Won't, and other characters who demonstrate the good will generated by nice manners.
3 8 11 13 19 26 36
Keywords: Behavior -- Fiction